General practice registrars’ clinical uncertainty, and in-consultation information- and assistance-seeking (Health Education in Practice: Journal of Research for Professional Learning, 2021)
Purpose: To explore the association of Australian general practitioner (GP) registrars’ responses to uncertainty with their in-consultation information-, advice- and assistance-seeking.Design/methodology/approach: A cross-sectional analysis of data from the Registrar Clinical Encounters in Training (ReCEnT) cohort study in four Australian states. In ReCEnT, GP registrars record details of 60 consecutive consultations, six-monthly, three times during training.Outcome factors in logistic regression models included whether the registrar sought in-consultation information or assistance from (i) their supervisor or (ii) an electronic or paper-based source. Independent variables were the four independent subscales of the Physicians’ Reaction to Uncertainty (PRU) instrument, as well as registrar, practice and consultation variables.Findings: 589 registrars contributed details of 70,412 consultations.On multivariable analysis, scores on the two ‘affective’ PRU subscales ‘anxiety regarding diagnosis/management’ (OR 1.03; 95% confidence intervals [CIs] [1.01, 1.05], p = 0.003) and ‘concern about a bad outcome’ (OR 1.03; 95% CIs [1.01, 1.06], p = 0.008) were significantly associated with seeking supervisor assistance. There was no association with ‘behavioural’ subscales ‘reluctance to disclose uncertainty to patients’ and ‘reluctance to disclose mistakes to physicians’.None of the PRU subscales were significantly associated with information-seeking from electronic or hard copy sources.Research implications: Further research is required to explore the role of uncertainty within registrar–supervisor interactions and to define the role of supervisors in registrars’ functional adaptation to clinical uncertainty (including how best to support and train supervisors in this role).Practical implications: GP registrars’ ‘affective’ responses to clinical uncertainty are associated with assistance-seeking from clinical supervisors. While in-consultation assistance-seeking may promote registrars’ tolerance of uncertainty, it may also contribute to supervisor workload.Originality/value: This is the first study to examine trainees’ levels of uncertainty and their seeking of information and assistance.Limitations: We have not investigated whether registrars’ seeking assistance resolved or attenuated, for the index problem, their anxiety or concern.